2017
DOI: 10.3390/ma10030263
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Seismic Performance of a Rigidly Connected Modular System Depending on the Shape and Size of the Ceiling Bracket

Abstract: Modular systems have been mostly researched in relatively low-rise structures but, lately, their applications to mid- to high-rise structures began to be reviewed, and research interest in new modularization subjects has increased. The application of modular systems to mid- to high-rise structures requires the structural stability of the frame and connections that consist of units, and the evaluation of the stiffness of structures that are combined in units. However, the combination of general units causes los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…6 shows the lateral bending capacity of joints. The procedure for determining the bending capacity of each joint was identical to that reported previously [17,28,31,32]. The developed joints were found to have a significantly higher lateral load-carrying capacity and seismic response than previously proposed joints [41,42].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…6 shows the lateral bending capacity of joints. The procedure for determining the bending capacity of each joint was identical to that reported previously [17,28,31,32]. The developed joints were found to have a significantly higher lateral load-carrying capacity and seismic response than previously proposed joints [41,42].…”
Section: Discussionmentioning
confidence: 72%
“…The seismic performance of each joint model was evaluated using the special moment frame (SMF) parameters, which were found to be consistent with the 0.04 rad rotational deformation capacity with a strength of 0.8MP [28,40]. All corner joint models met the drift angle accumulation criteria of 0.04 rad and the required bending moment capacity (except S3 with a 0.92 ratio).…”
Section: Seismic Performance Of Jointsmentioning
confidence: 96%
See 1 more Smart Citation
“…The second highest ranked risk item according to RII values calculated in Table 3 is DR5 (i.e., insufficient design code for joints between prefabricated components). It has been emphasized and evaluated in multiple studies (e.g., Kim et al, 2017;Lee et al, 2017;Park et al, 2017) of the connection joints between modular members. In contrast, the two general risk items (i.e., GR1 and GR2) were perceived as least likely to occur among the 14 risk items.…”
Section: Probability Of Risks Involved In Implementing Osc In the Idc Project Deliverymentioning
confidence: 99%
“…investigated the bearing capacity of a full-scale modular unit under vertical and lateral loadings by using means of tests and FE analysis [28]. The studies previously recorded were found to be confined to the performance of corner joints, simplified frames or modular units without any proper detailed behaviour of connections, use of weaker sections and access holes, while, very least attention was paid to the behaviour of complex form of joints, i.e., middle joint, simplification of the joint to overcome computational efforts, combined effect of forces on the behaviour of modular units with the developed joint and the overall dynamic response of MSB against real earthquake accelerograms [8,24,25,27,29,30]. The main aim of the current study was to develop a newtype of bolted joint, analyse its bending performance, simplify and apply it in the full-scale modular units, and evaluate the overall seismic performance of the developed simplified multi-storey MSB.…”
Section: Introductionmentioning
confidence: 99%